Pengaruh Profitabilitas, Likuiditas, Struktur Aset, dan Kebijakan Dividen Terhadap Struktur Modal : Studi kasus perusahaan manfaktur terdaftar di BEI periode 2018 - 2022 - Marpaung, bintangsahala0203; Marpaung, DR Annaria Magdalena; Hasibuan, DR David H.M.; Hilman Fauzi (Media Ilmiah Akuntansi, 2024)
This research aims to determine whether there is an influence or not on the Profitability, Liquidity, Asset Structure, and Dividend Policy ratios towards Capital Structure in Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. The sample in this study consists of 9 companies selected using purposive sampling technique. With purposive sampling technique, a total of 9 companies with a 5-year period were obtained, resulting in a total of 45 data points for this study. The analysis method used in this research is descriptive statistics, preceded by the Classical Assumption Test. If the data is normally distributed, multiple linear regression analysis can be used, along with the T-test and F-test (simultaneous) and the Coefficient of Determination test using SPSS 25. The partial results of this study indicate that Profitability does not significantly affect Capital Structure, while Liquidity has a positive influence.